Pengaruh Brand Image dan Customer Satisfaction Terhadap Word of Mouth di Krisna Oleh-Oleh Khas Bali - wirawan, dodik gede; Wibawa, I Made Artha (E-Jurnal Manajemen; Vol 1 No 1 (2012), 2012)
This study aims to determine the effect of brand image and customer satisfaction on word of mouth. The research was conducted in Krishna souvenirs typical of Bali in Denpasar with a population of consumers who shop at Krishna souvenirs typical of Bali. Purposive sampling with sampling with 110 respondents. Analysis of the data used is path analysis. Based on the results of the study found that the direct influence which indicates a stronger brand image will improve customer saisfaction and word of mouth. Similarly, the indirect effect shows that the stronger the brand image will enhance word of mouth through customer satisfaction. The implications of the research is need to do major repairs on the variables of brand image and customer satisfaction in order to marketing via word of mouth about Krisna souvenirs typical of Bali can be improved, so a medium for communication and effective marketing for the company's progress and facing increasing competition. keyword : Brand image, customer staisfaction, word of mouth
Keywords: id